Means of forming a healthy way of life for employees of banking establishments - В.М. Лисяк (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
In this paper we consider the peculiarities of labor, the activation of the mental functions of employees of the banking institution. Traces the socio-psychological and motivational effects of labor on the health of workers. The special features of healthy lifestyle management by banking institutions based on the analysis of a comprehensive questionnaire, the main factors and reasons that hinder a healthy lifestyle are explained. The physical activity of the employees of the banking institution is determined in view of the specific nature of the work. A comparative description of the importance of conducting a healthy lifestyle and the general state of health of bank employees and students is developed. The factors influencing the health and physical activity of the workers are investigated. Investigational factors are influence on a health and physical activity of workers. The most ponderable factor of risk of influInvence on the bodily condition of bank workers are psychological conflicts which need to be removed by rehabilitation exercises.